Practical Value of Sight Reduction Tables - Kotlarić, Stjepo M. (The International Hydrographic Review, 2015)
It is a well-known fact that there are many tables published to assist navigators in finding a ship's position from observations of celestial bodies. In the I.H.B.'s Hydrographic Review, issued in August 1943, in the article "Chronological and Analytical List of various Tables or Treatises on Navigation intended to facilitate Nautical Computations and accelerate ship's position finding" , by Captain H. Bencker, there appeared an extensive account (80 pages) of the various means and methods published up to the year 1942 for navigational purposes and for finding a ship's position at sea. For the most important tables an explanation about the method and formulae on which they were based was given. A valuable and fairly extensive review (56 pages) of the various methods, tables, and graphical and mechanical solutions of the position line, as well as direct solutions for a celestial fix published before 1957 is given in chapter XXI of the H.O. Pub. No. 9 "American Practical Navigator" by N. Bowditch, 1958 edition. The question inevitably arising in this connection is : How may we find out which is the best method to use in actual practice ? This paper deals with the method of determining the practical value of sight reduction tables. In addition, as an illustration of this method and its practical applications, an assessment has been made of the Tables K 1 (representing the short method of two-entry tables for the computation of the altitude and azimuth of celestial bodies) issued by the Hydrographic Institute of the Yugoslav Navy at the end of the year 1958.